PROSES PEMBUATAN HOUSING BEARING GEARBOX 3Z2M21 DENGAN MATERIAL FCD 400 - Abdul Rahman Agung Ramadhan; Eko Aprianto Nugroho (Asosiasi Dosen Muda Indonesia, 2023)
Fundamental, detailed and in-depth understanding of technology is carried out through the use of concrete pumps used to move fluid from one place to a higher place, high pressure and circulation. One of the important components of the pumping system in the industry is the Gearbox Bearing Housing which functions as a bearing housing so that the bearing can move and continue the shaft work system on the pump. The material used to make the Gearbox Bearing Housing is based on FCD 400. The manufacturing process for the Gearbox Bearing Housing is a lathe where in this process the workpiece is fed by rotating the workpiece and then touching it to a chisel which is moved in translation parallel to the axis of rotation. of the workpiece. The outer diameter is 700 mm, while the inner diameter is 340 mm and D2 is 440 mm. Drilling Machine Process, the machining process is the process of expanding or enlarging a hole that can be done with a drill bar. For the size of the holes, namely the diameter of 22 mm as many as 16 holes, the diameter of 20 mm as many as 16 holes and for the diameter of 12 mm there are 4 holes. Grinding Machine Process is a finishing process that is used to remove parts of the workpiece that are uneven. In the manufacture of Gearbox Bearing Housing, checks are carried out on the workpiece to determine whether or not an item is produced. If the workpiece is said to be feasible, it will be packaged to be marketed, if not, the workpiece will be destroyed.